Facilitators and barriers to providing affirming care for transgender patients in primary care practices in Arkansas. Issue 1 (29th May 2022) - Marshall, Sarah Alexandra; Stewart, Mary Kathryn; Barham, Caroline; Ounpraseuth, Songthip; Curran, Geoffrey
Abstract: Purpose: This study assessed factors affecting the provision of affirming‐care best practices (ACBPs) for transgender individuals by primary care providers (PCPs) in a rural, southern state Methods: We conducted a sequential explanatory mixed‐methods study in 2020, including a statewide survey (phase 1) and interviews (phase 2). Surveyed PCPs (phase 1) included Medical Doctors/Doctors of Osteopathy (MDs/DOs), nurse practitioners, and 1 physician assistant. Interview participants (phase 2) included providers and staff in 6 practices throughout the state. We used an exploratory approach to data collection and performed content analysis to classify interview data into categories representing overarching themes Results: Among surveyed PCPs who reported they had provided care to transgender patients (n = 35), the most common reason for providing gender‐affirming medical services was "because of my ethical obligation to treat patients equally" (n = 27, 77%). The most common reason for not providing such services was because the PCPs "have not been trained/don't feel competent to provide these services" (n = 12, 34%). Interviews revealed the following themes: (1) willingness to provide "culturally competent care"; (2) continuum of accepting to affirming attitudes toward transgender individuals; (3) basic understanding of stigma and an awareness of its impact; (4) changes needed to provide "culturally competent care"; and (5) preferred clinical support strategies. Conclusion: Training and education to provide ACBPs are warranted and would meet the needs of patients and providers. Facilitating telemedicine visits for transgender patients with gender‐affirming care experts was a favorable implementation strategy for clinical support and is recommended to address access to affirming care.